Code Mixing in Youtube Video Content of Gen Halilintar in 2019 - Zulfatriani Isra; Dakia N. Djou; Fatmah AR. Umar (Universitas Negeri Gorontalo, 2022)
This study was aimed to identify the forms and causative factors of Code Mixing in YouTube Video Content of Gen Halilintar in 2019, by employing qualitative descriptive approach. The data was obtained from Gen Halilintar as the speaker in their YouTube Video Content in 2019, which was collected by observation and data transcription technique by identifying the observation results, sorting the results based on Code Mixing forms, analyzing the data, presenting the data, and withdraw conclusions. The findings revealed 158 data of Code Mixing from 12 YouTube videos that includes 4 forms: words, phrases, clauses, and sentences. The causative factors consists of Code Mixing limitation of use, popular use of terms, speaker and his/her personality, speaker's partner, residence, modus of discussion, topic, goals and benefits, variants an and level of speech, third speaker's presence, the act of stimulating humor, and the act of mere bragging. This study concludes with words as the most used form of code mixing of all 4 forms, while the most indluencing factor is residence.